The Effect of Problem-Solving Skills Training Based on Personal Competencies on Self-Efficacy Beliefs and Epistemological Beliefs in Adolescents - Nourbakhsh, Seyed Vahid; Alizadehfard, Susan; Davoodi, Abdolvahid (Mental Health and Lifestyle Journal, 2024)
Self-efficacy beliefs and epistemological beliefs are considered fundamental factors in students' academic and cognitive development. The aim of the present study was to examine the effectiveness of problem-solving skills training on adolescents' self-efficacy beliefs and epistemological beliefs. This study employed a quasi-experimental method using a pretest-posttest design with a control group. The sample consisted of secondary school students who were randomly assigned to experimental and control groups. The experimental group received six 90-minute sessions of problem-solving skills training, while the control group continued their regular educational activities. Data collection tools included the General Self-Efficacy Scale developed by Sherer et al. (1982) and the Epistemological Beliefs Questionnaire by Newmann and Conrad (2000). Data were analyzed using analysis of covariance (ANCOVA). The results indicated that problem-solving skills training had a significant effect on increasing students' self-efficacy beliefs and enhancing their epistemological beliefs (p < .05). The posttest mean scores of the experimental group in both variables were significantly higher than those of the control group. Problem-solving skills training can be utilized as an effective strategy for improving self-efficacy beliefs and strengthening epistemological beliefs in students. Empowering students through problem-solving skills training leads to cognitive growth, increased responsibility, and more informed decision-making.